Programma: 12 oktober Walter Trout Band; 13 oktober Green Day; 14 oktober Captain Gumbo; 15 oktober New Bomb Turks, Laika & The Cosmonauts
Programma: 12 oktober Walter Trout Band; 13 oktober Green Day; 14 oktober Captain Gumbo; 15 oktober New Bomb Turks, Laika & The Cosmonauts.